PENGARUH BEBAN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI BIRO KERJASAMA TEKNIK LUAR NEGERI DI KEMENTERIAN SEKRETARIAT NEGARA - Febriastuti, Riska; Dwimawanti, Ida Hayu; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
This study was conducted at the Overseas Technical Cooperation Bureau, Ministry of State Secretariat. The purpose of this study is to describe and analyze workload, motivation and employee performance, to test the influence of workload towards employee performance, to test the influence of motivation towards employee performance, and to test the influence of workload and motivation towards employee performance at the Overseas Technical Cooperation Bureau, Ministry of State Secretariat. The research method was qualitative research method. The data in this study were gained through questioner and interview. In analyzing the data, the writer used Kendall Correlation Coefficient, Kendall Concordance Coefficient, and Determination Coefficient. The result of this study showed that the employee performance of the Overseas Technical Cooperation Bureau, Ministry of State Secretariat was not good. The result of this study showed that the workload of the Overseas Technical Cooperation Bureau was not good. The result of this study showed that motivation of the Overseas Technical Cooperation Bureau was not good. The influence of workload towards employee performance was 14,28%. The influence of motivation towards employee performance was 19,80%. The influence of workload and motivation towards employee performance was 1,02 and the other 98,98% was effected by other factors. The result showed that there was positive and significant correlation between workload and motivation towards employee performance. Conclusions in this research third variable that is the employee performance, workload and motivation are still said to be less good. It is viewed from the work of nonconformity with a standard, less mampunya employees in understanding a task, of the division of work because of limited human resources, and the absence of the awards for employees who work with both, diligent and discipline. From this research and the author gives advice of the need of training the operation of database input for employees because of the system change, the need of additional employees to workload no weight and need to increase the motivation through the award.